Eliminating the White Supremacy Mindset from Global Health Education - Agnes Binagwaho; Brianna Ngarambe; Kedest Mathewos (Ubiquity Press, 2022)
The term "decolonization" has been increasingly used to refer to the elimination of the colonial experience and its legacy. However, the use of this overarching term masks the real root of the problem. European countries, whose populations are majority white, used their assumed supremacy as justification for the colonization of current low- and middle-income countries (LMICs) where the majority of non-white people live. This clear overlap between geographic and skin color differences explains how the white supremacy ideology triggered European colonization. Therefore, calls to decolonize global health education must focus on the roots of colonization and fight for the elimination of white supremacy ideology that is one of the pillars of the current ills of our global health architecture. A step in this process acknowledging the expertise that emerges from LMICs, alongside challenging the traditional high-income country (HIC) hegemony over knowledge and strengthening universities in LMICs to provide quality medical and global health education. Additionally, we also need to reevaluate curricula, research selection, and design as well as partnerships. Students need to be equipped with the skills to question norms and contribute to the creation of equitable, mutually beneficial partnerships. This needs to accompanied by the adoption of transdisciplinary education to address critical societal challenges. By challenging the white supremacy ideology, we can shift the center of gravity in global health to respect the right to equal say in education and research according to the disease burden and the distribution of the world population.